RELEVANCE OF MATERNAL FACTOR ON LOW BIRTH WEIGHT IN FULL-TERM NEONATES AT NAKIVALE HEALTH CENTER III, ISINGIRO DISTRICT.A CROSS-SECTIONAL STUDY. - Ayesigye, Iran; Turumanya, Judah; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2024)
Background Low birth weight (LBW) among neonates constitutes a significant global public health challenge with implications for immediate and long-term maternal and child health outcomes. This study investigated the relevance of maternal demographic factors on LBW neonates: specifically focusing on the association of maternal age, residential category status, and the relationship between gravidity and parity, and health status with low birth weight in full-term neonates at Nakivale Health Center III, Isingiro district. Methodology The study adopted a descriptive cross-sectional research design conducted among 98 mothers. The data was collected from the maternal register and analyzed using descriptive, exploratory, and logistic regression analysis. Results The average age of mothers was approximately 25.37 years, A logistic regression model fitted to explore the simultaneous influence of multiple maternal demographic factors on the likelihood of LBWs recorded Age = 0.779, Gravidity = 0.997, Parity:p = 0.997, Nulliparity: (Yes vs. No): p = 1.000. The null model's null deviance was 93.4760 with 97 degrees of freedom, all participants were recorded with an HIV-negative status and the average weight of babies was 2.247 Kg, with a range from 1.5 to 2.4 Kg. Conclusion The study offered valuable insights into the factors potentially influencing LBW at Nakivale Health Center III. While maternal age, residential category, gravidity, and parity were explored, only maternal age showed no significant association with LBW Recommendation To improve the accuracy and depth of our findings, health centers should prioritize complete and comprehensive data collection, especially concerning maternal health statuses. Culturally sensitive interventions focusing on socioeconomic inequalities, timely access to antenatal and prenatal care, and health education promotion will be crucial in reducing LBW incidence and improving maternal and child health outcomes.